Chapter Sign language ideologies: Practices and politics - Kusters, Annelies (Sign Languages and Deaf Communities [SLDC], 2020)
This book focuses on how sign language ideologies influence, manifest in, and are challenged by communicative practices. Sign languages are minority languages using the visual-gestural and tactile modalities, whose affordances are very different from those of spoken languages using the auditory-oral modality.